2013
DOI: 10.1136/flgastro-2013-100393
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an endoscopy safety checklist

Abstract: Patient safety and quality improvement are increasingly prioritised across all areas of healthcare. Errors in endoscopy are common but often inconsequential and therefore go uncorrected. A series of minor errors, however, may culminate in a significant adverse event. This is unsurprising given the rising volume and complexity of cases coupled with shift working patterns. There is a growing body of evidence to suggest that surgical safety checklists can prevent errors and thus positively impact on patient morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 15 publications
3
40
0
2
Order By: Relevance
“…The endoscopy team is well defined yet the roles and responsibilities are not always clearly articulated particularly in complex scenarios with extended teams, for example, emergency cases conducted in the operating theatre. Practical patient safety tools to enhance teamwork communication such as the endoscopy safety checklist are used by many units22 and now recommended by JAG. Team briefings and debriefings at the beginning and end of a list have the potential to identify, avert and prevent recurrent safety issues and educate different members of the team (administrative, management, nursing medical and surgical).…”
Section: Future Potentialmentioning
confidence: 99%
“…The endoscopy team is well defined yet the roles and responsibilities are not always clearly articulated particularly in complex scenarios with extended teams, for example, emergency cases conducted in the operating theatre. Practical patient safety tools to enhance teamwork communication such as the endoscopy safety checklist are used by many units22 and now recommended by JAG. Team briefings and debriefings at the beginning and end of a list have the potential to identify, avert and prevent recurrent safety issues and educate different members of the team (administrative, management, nursing medical and surgical).…”
Section: Future Potentialmentioning
confidence: 99%
“…Adaptations of such checklists are being proactively adopted by many endoscopy units 13. Although there is no proof of similar efficacy of such checklists in endoscopy units to the theatre environment nor of the ideal format, early adopters have confirmed that such adapted checklists reduce the opportunity for error, facilitate whole team communication and allow patient involvement—for example, through reconfirmation of consent.…”
Section: Patients Considered To Have Capacitymentioning
confidence: 99%
“…Another aspect of quality improvement that we can learn from in endoscopy is the improvements in surgical safety brought about by the introduction of checklists. The St Mark's group have implemented such an endoscopy unit checklist and Matharoo et al 3 describe the lessons learned from their experience. As well as sharing the checklist itself they also provide a videolink to demonstrate its utility and potential to improve safety and teamwork.…”
Section: Real-life Experience To Improve Endoscopy Outcomes: Optimisimentioning
confidence: 99%